2017
DOI: 10.17221/18/2016-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of dental panoramic radiography for dental arch evaluation in small animals

Abstract: The purpose of this study was to evaluate the feasibility of dental panoramic radiography for dental arch evaluation in small animals. The dental arches of four Beagles, one Shih Tzu dog, and three Korean short-haired cats were radiographed using human panoramic X-rays. All animals were under general anaesthesia during the examination. The animals’ heads were placed horizontal to the panoramic device, just as a human’s head is placed in panoramic dental assessments. All animals were evaluated with an open and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The feasibility of dental panoramic imaging for dental arch evaluation in small animals has been previously investigated (5). In the present study, a single panoramic view was found to be unsuitable for evaluation of the entire skull of the cat due to the inability to include all anatomic structures of interest in a single curved plane without superimposition of anatomic structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The feasibility of dental panoramic imaging for dental arch evaluation in small animals has been previously investigated (5). In the present study, a single panoramic view was found to be unsuitable for evaluation of the entire skull of the cat due to the inability to include all anatomic structures of interest in a single curved plane without superimposition of anatomic structures.…”
Section: Discussionmentioning
confidence: 99%
“…The use of rapid scan technology, which allows for faster image acquisition than conventional CT, and the ability to post process the volumetric data into various 2-D and 3-D reconstructions, makes CBCT an attractive imaging modality. Currently, validation of the clinical application of CBCT in veterinary patients is ongoing (512), and more research is required to validate the use of CBCT to responsibly promote its use in routine veterinary clinical practice.…”
Section: Introductionmentioning
confidence: 99%